Information needs for liver transplantation recipients - Luciana da Costa; Mendes, Karina Dal Sasso; Matins-Pedersoli, Tatiane; Molina, Fabiana Murad Rossin; Galvão, Cristina Maria (Brazilian Journal of Transplantation, 2021)
Purpose: Assessing the information needs to liver transplant recipients in outpatient hospital care. Method: Descriptive study conducted in a Brazilian transplant center. The sample consisted of 92 participants. Data collection was performed over a five-month period, with application of an adapted instrument. Results: The information needs that obtained the highest averages were: complications after transplantation (5.35), medications after surgery (5.29), and food intake after transplantation (4.53). The information needs that obtained lower averages were related to pregnancy and contraception (0.28), social and leisure activities (0.89), and return to work / study (0.97). Conclusion: The resulting knowledge on the information needs can help in planning educational interventions, which can improve the quality of care, treatment adherence and prevention of complications after transplantation.